The Role of Glucocorticoids in the Management of COVID-19 - Alexaki, Vasileia Ismini; Henneicke, Holger (Hormone and Metabolic Research, 2020)
Coronavirus disease 2019 (COVID-19), caused by an infection with the novel coronavirus SARS-CoV-2, has resulted in a global pandemic and poses an emergency to public health systems worldwide. COVID-19 is highly infectious and is characterized by an acute respiratory illness that varies from mild flu-like symptoms to the life-threatening acute respiratory distress syndrome (ARDS). As such, there is an urgent need for the development of new therapeutic strategies, which combat the high mortality in severely ill COVID-19 patients. Glucocorticoids are a frontline treatment for a diverse range of inflammatory diseases. Due to their immunosuppressive functions, the use of glucocorticoids in the treatment of COVID-19 patients was initially regarded with caution. However, recent studies concluded that the initiation of systemic glucocorticoids in patients suffering from severe and critical COVID-19 is associated with lower mortality. Herein we review the anti-inflammatory effects of glucocorticoids and discuss emerging issues in their clinical use in the context of COVID-19.
Keywords: glucocorticoids inflammation COVID-19